VISUALS: Beyond Nationalism The visual culture of Fresco's expressionism, a case of the Shekhawati region: Exploring the Visual Culture and Urban Development of Shekhawati through Frescos (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The historic medieval towns of the Shekhawati region are culturally rich with their uniqueurban morphology and painting expression. The Shekhawati towns describe their virtual boundaries bythree districts – Churu, Jhunjhunu, and Sikar. However, the largely identified towns within these districtsas urban clusters are Mandawa, Nawalgarh, Fatehpur, Ramgarh, Mukundgarh, and Lakshmangarh. Theseare interpreted towns as my area of focus for this paper writing. Here, this piece document will bepresented with an idea of exploring and recording the experience of urbanity through different urbanvisual cultures in this region. Furthermore, the focus of the study concentrated on the urbandevelopment shift because of East India Company Governments from 18-19th century. Industrializationand Colonization brought transformation to Indian urban culture and exploration of new ideas across theIndian subcontinent. This time frame and shift of revival in Shekhawati urban visual will be the centralidea of recording and establishing the relationship of visuals with the culture and urban morphologicallandscape as a method of this paper writing. These cluster has a vibrant culture which states thesignificance of the whole region. The exploration of urbanity will be largely analyzed with the town’srecord historically, the merchant’s role in shaping the visual urbanity of mural paintings, the notion ofhomeland, visual reflection of urban morphology, an artistic expression, re-contextualization with urban,the outstanding cultural significance of towns with a visual painting of frescos, that will generate andexpress the painted murals experiences as an idea of urbanity. Hence, the outcome will be focused oncollected frescos’ world images and pictures as the visual of the towns. Further, the visual inferencespotentially can be the source of the Indian cultural knowledge system which can stand out from theworld.